Decolourisation of dyes in wastewater using adsorbent materials / Norfazilawati Che Daud - Che Daud, Norfazilawati (2009)
Nowadays, the effluent from textile industry has become one of the major pollutants that affect the water quality of Malaysian rivers. Wastewater from the textile industry needs to be treated before release to the water system to avoid the pollutants. Adsorption technique using adsorbent material from natural waste has been reported to be an alternative to activated carbon to treat the wastewater especially for the colour removal of dyes from the wastewater. The potentials adsorbents which are low cost, locally available and relatively new for their colour removal capacity from aqueous solution were investigated. Sugarcane Bagasse, Eggshells, Tea Wastes and Crab Shells were selected used as adsorbent materials to adsorb the Acidol Red GLX, Supra Yellow RL, Begacron FBL 150% and actual wastewater. The efficiency of the adsorbent materials in treating the wastewater were analysed before and after decolourising treatment based on the colour reduction, COD, and pH value. The result shows that crab shells give excellent adsorption capability as adsorbents material to adsorb dyes effluent. It is proposed that removal of dye in wastewater using these adsorbent materials can be attractive option for dye adsorption.